Participants’ Engagement With Telephone Support Interventions to Promote Healthy Feeding Practices and Obesity-Protective Behaviours for Infant Obesity Prevention - Ekambareshwar, Mahalakshmi; Xu, Huilan; Rissel, Chris; Baur, Louise; Taki, Sarah; Mihrshahi, Seema; Wen, Li Ming (Frontiers in Endocrinology, 2022)
Abstract Background: Participant engagement with program interventions is vital to support intended behaviour changes and outcomes. The aim of this research was to investigate participant engagement with the Communicating Healthy Beginnings Advice by Telephone (CHAT) program, an early childhood obesity prevention program that included interventions for promoting healthy infant feeding practices and obesity-protective behaviours via telephone, and whether engagement with the telephone support program varied by participants’ sociodemographic characteristics. Methods: This study used de-identified CHAT program data of participants who received the interventions via telephone. Data analysed included 1) participant engagement in telephone support from late pregnancy to 12 months of age, 2) demographic characteristics collected at late pregnancy and 3) intervention providers’ observations and notes (qualitative data) for 10 participants from each engagement group (low, medium, high) to explore issues discussed during telephone support. Results: Call completion rate by participants was above sixty percent for all six stages of the telephone support program with more than half of the participants (57%) demonstrating high level of engagement. We found that participants’ country of birth, employment status and annual household income were predictors of engagement with the telephone support provided in the CHAT program. The odds of participants’ engagement with the telephone support program were 1.68 times higher for Australian born (95% CI 1.07 – 2.62), 1.63 times higher for participants who were employed (95% CI 1.01 – 2.66) and 1.63 times higher for participants with annual household income ≥AUD$80,000 (95% CI 1.02 – 2.60). Conclusions: Participant engagement with the program interventions was good. Participants’ engagement with the telephone support program was significantly associated with certain socio-demographic characteristics. Although not an intended benefit of the intervention, psychosocial needs of participants were met which was a likely factor for mothers’ engagement with the program. This is an important factor that needs to be considered while implementing future programs or scale up of this program. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership. References should not be cited in the abstract.